Mathematics c Michael Kenwood, Cyril Moss - Kenwood, Michael; Moss, Cyril (Longman A-level and AS-level revise guides, 1995)
"Longman Revise Guides" have been written and compiled by the people who set GSCE papers and mark them - the examiners. They cover exactly what students need to know, understand and revise in each subject for maximum success, so that students can approach their exams with confidence. Each book gives expert advice in planning a revision programme effectively: how students should pace themselves, how to make the most of their time and energy and how to make continous assessment really work. This edition of the "Revise Guide" has been revised and updated to cover the new syllabuses. Teaching begins in September 1995, with the first exams being taken in June 1997. Special features include: syllabus breakdown and analysis; coursework preparation and presentation; principles and applications; examiner commentary throughout; exam questions and specimen answers; typical student's answers - with the examiner's opinion and comments; and pull-out review sheets at the end of the most topic-based chapters.